Similarity in recombination rate and linkage disequilibrium at CYP2C and CYP2D cytochrome P450 gene regions among Europeans indicates signs of selection and no advantage of using tagSNPs in population isolates - Pimenoff, Ville N.; Laval, Guillaume; Comas, David; Palo, Jukka; Gut, Ivo; Cann, Howard N.; Excoffier, Laurent (Pharmacogenetics and Genomics, 2012)
[OBJECTIVE] Linkage disequilibrium (LD) and recombination rate variations are known to vary considerably between human genome regions and populations mostly because of the combined effects of mutation, recombination, and demographic history. Thus, the pattern of LD is a key issue to disentangle variants associated with complex traits. Here, we aim to describe the haplotype structure and LD variation at the pharmacogenetically relevant cytochrome P450 CYP2C and CYP2D gene regions among European populations. [METHODS] To assess the haplotype structure, LD pattern, and recombination rate variations in the clinically significant CYP2C and CYP2D regions, we genotyped 143 single-nucleotide polymorphisms (SNPs) across these two genome regions in a diverse set of 11 European population samples and one sub-Saharan African sample. [RESULTS] Our results showed extended patterns of LD and in general a low rate of recombination at these loci, and a low degree of allele differentiation for the two cytochrome P450 regions among Europeans, with the exception of the Sami and the Finns as European outliers. The Sami sample showed reduced haplotype diversity and higher LD for the two cytochrome P450 regions than the other Europeans, a feature that is proposed to enhance the LD mapping of underlying common complex traits. However, recombination hotspots and LD blocks at these two regions showed highly consistent structures across Europeans including Finns and Sami. Moreover, we showed that the CEPH sample has significantly higher tag transferability among Europeans and a more efficient tagging of both the rare CYP2C9 and the common CYP2C19 functional variants than the Sami. Our data set included CYP2C9*3 (rs1057910) and CYP2C19*2 (rs4244285) enzyme activity-altering variants associated in a recent genome-wide study with acenocoumarol-induced and warfarin-induced anticoagulation or to the antiplatelet effect of clopidogrel, respectively. Including these known activity-altering variants, we showed the haplotype variation and high ...